Personality determinants of consumption of premium seats in sports stadiums. Issue 8 (12th August 2019) - Chang, Yonghwan; Ko, Yong Jae; Jang, Wonseok (Eric)
Abstract : Purpose: The current study aims to develop a comprehensive hierarchical model of traits and needs to provide a theoretical understanding of personality determinants of luxury-services consumption. Design/methodology/approach: The sample comprised 415 single-event buyers of premium seats in sports stadiums. The causal relationships of hierarchically ordered four traits – elemental, compound, situational and surface – were examined. Findings: Extraversion was found to be an important trait for needs for material resources and status, while conscientiousness and openness were important predictors of need for arousal. Furthermore, needs for material resources, status and uniqueness were found to be important for self-value consciousness. Self-value consciousness was found to be an important predictor of purchase intention. Originality/value: The study integrates fragmented luxury services research on individual differences. The findings about the personality determinants would provide relatively consistent predictions behind luxury-services consumption potentially applicable to diverse luxury markets.